(untitled) (Bangladesh Veterinarian, 2018)
Study was conducted to observe the influence of different factors on pregnancy rate in 24 indigenous ewes following artificial insemination (AI) with frozen semen. The ewes were synchronized by intra-muscular injection of Prostaglandin F2α (Ovuprost® Bayer, New Zealand). The onset and intensity of oestrus were determined by oestrus behaviour of ewes with vasectomized ram. VER values were measured immediately before AI using electrical heat detector (DRAMINSKI®, Owocowa 17, Poland). Twelve ewes were inseminated trans-cervically and 12 laparoscopically. Five ewes were treated with Misoprostol (Cytomis® 200 µg tablet; Incepta Pharmaceuticals Ltd. Bangladesh) to relax the cervix 12 hours before TCAI, and cervical penetration depth was measured by a steel rod. Pregnancy was confirmed by ultrasonography at 40 – 45 days after AI. Cervical penetration depth was significantly increased (P<0.05) (0.48 ± 0.04 vs. 3.52 ± 0.17 cm) in treatment group. The pregnancy rate tended to be higher in treatment group (60.0 vs. 28.6%). In treatment group cervical penetration was significantly increased (P<0.05) (0.35 ± 0.08 vs. 3.52 ± 0.17 cm) immediately before AI compared with before oestrus synchronization. The pregnancy rate was significantly higher (P<0.05) (75.0 vs. 28.6%) in LAPAI than TCAI without treatment. The pregnancy rate tended to be higher (75.0 vs. 55.6%) in ewes with high oestrus intensity than in those with medium intensity. The pregnancy rate was significantly higher (P<0.05 : 70.0 vs. 20.0%) in lower VER group (230 - 280 Ω) compared with higher VER group (331 – 380 Ω.) Although LAPAI was superior to TCAI, TCAI in ewes treated with misoprostol giving a pregnancy rate of 60% could be acceptable, until the LAPAI could be made simpler to be used in field. The oestrus intensity and low VER values could be used to select ewes to be inseminated to increase the pregnancy rate. Bangl. vet. 2016. Vol. 33, No. 2, 33-38